2013
DOI: 10.1682/jrrd.2012.07.0134
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged electrical stimulation-induced gluteal and hamstring muscle activation and sitting pressure in spinal cord injury: Effect of duty cycle

Abstract: Abstract-Pressure ulcers (PUs) are highly prevalent in people with spinal cord injury (SCI). Electrical stimulation (ES) activates muscles and might reduce risk factors. Our objectives were to study and compare the effects of two duty cycles during 3 h of ES-induced gluteal and hamstring activation on interface pressure distribution in sitting individuals with SCI and study the usability of a newly developed electrode garment (ES shorts). Ten individuals with SCI participated in this study, in which two ES pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Some techniques for preventing pressure ulcers have been focused on gluteal muscle stimulation through functional electrical stimulation [29,30]. These techniques have reported pressure redistribution over different zones of the seat as well as a promotion of blood flow in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Some techniques for preventing pressure ulcers have been focused on gluteal muscle stimulation through functional electrical stimulation [29,30]. These techniques have reported pressure redistribution over different zones of the seat as well as a promotion of blood flow in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the variability between individuals, the current amplitude was subjectively determined by the researcher and individualized for each participant with increments of 5 to 10mA to a level that did not cause discomfort or excessive movement. To minimize muscle fatigue and ensure continuous muscle contractions, a 1:4 duty cycle, consisting of 1-second stimulation followed by 4 seconds without stimulation for a period of 3 minutes was used 14 .…”
Section: Methodsmentioning
confidence: 99%
“…during awake hours). Using this approach, an acute bout of FES to the gluteal and hamstring muscles has shown to reduce pressure over the ischial tuberosity 14 and increase transcutaneous oxygen levels 15 . To date, no study has directly examined the acute impact of FES using a wearable clothing garment on both microand macro-vascular perfusion in people with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…While there has been little research on electrical stimulation, evidence has shown many benefits of its use. Patients have seen improvements in functional performance 27,30,32,38 , muscle reeducation following ACL reconstruction 28 , increased blood flow [6][7][8][9]16,18,19,[22][23][24]26,29,31,33,34,36,41,42 , reduced neuromuscular activation deficits 16,17,20,21,24,26,28,30,32,37,38,42 , pain reduction and improved psychological wellbeing.…”
Section: Benefits Of Electrical Stimulationmentioning
confidence: 99%
“…2 These treatment goals may be related to treating conditions that include spinal accessory nerve injury 16 , spinal cord injury 21 , sprains, strains and joint dysfunction. Among the specific indicated uses of motor level electrical stimulation are pressure ulcers 18,33,36,38 , reeducation of muscles following surgery 28 and treatment of nerve dysfunction. 2,17,22,27 Muscle activation by electrical stimulation for prevention of pressure ulcers (PUs)…”
Section: Muscular Contraction By Electrical Stimulationmentioning
confidence: 99%